Successful Black entrepreneurs : hidden histories, inspirational stories, and extraordinary business achievements : case studies by Harvard Business School - Rogers, Steven, 1957- (John Wiley & Sons, Inc., 2022)
"A few years ago, while serving as a Professor at Harvard Business School, Rogers created a new course titled "Black Business Leaders and Entrepreneurship." After learning of the new course, a white professor asked, "Why do we need this course? What is the difference between Black and white entrepreneurs?" In response, Rogers identified the following differences: Black entrepreneurs cannot access capital from traditional financial institutions including banks and private equity firms Many Black entrepreneurs who want to sell to white customers must practice "racial concealment" to be successful Successful Black entrepreneurs who are not athletes or entertainers are virtually invisible in the minds of the general public All of these reasons have a negative impact on Black entrepreneurship which hurts the Black community and the entire country. Successful Black entrepreneurs create jobs for Black, white, and other racial groups. They also have created companies that provide products and services that has benefited society-at-large. For the Black community, Black entrepreneurship has been synonymous with freedom and self-sufficiency. For example, Black entrepreneurs are the largest private employers of Black people in the country. The government is the top public employer. The book will be largely comprised of case studies that Rogers wrote and have been published by Harvard Business School (HBS). These are all case studies that have been individually sold by Harvard Business Publishing, proving that there is a market for this content. A book made up primarily of HBS case studies about Black entrepreneurs has never been published"--